Frequency effects in the production and perception of long vowels in Turkish - Sarıgül, Özge. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2011., 2011)
This study aims to understand whether the linguistic experience of Turkish speakers have an effect on their knowledge of the phonology of their language and linguistic processes like production and perception. The representation of lexically specified vowel length in borrowed words is chosen due to its special status in Turkish. This type of length in Turkish is not optional or predictable and gives rise to variation and confusion among speakers. This study consists of two experiments with nonce words and a pronunciation survey designed to understand two types of frequency effects; i) prototype effect ii) exemplar effect in the processes of production and perception of long vowels in Turkish. In order to uncover the prototypical word with long vowels in Turkish, 1722 words with lexically specified vowel length have been sorted out from the official Turkish Language Dictionary (TDK, 1974) and analyzed in terms of i) the syllable number and structure of words, ii) the vowel of the syllable following the long vowel iii) the consonant preceding or following the long vowel. In order to reveal the exemplar effect, phonological neighborhoodness is used. Results suggest that there is a correlation between production and perception of long vowels in Turkish and the linguistic experience of the speakers. When both types of frequency effects i.e. frequency of patterns and lexical neighborhoodness are used creating nonce words, the versions with long vowels are favored. When they are used independently lexical neighborhood effect appears to be more powerful than the effect of frequency of patterns.
Keywords: Turkish languages -- Vowels.